ANALISIS SISTEM PENGENDALIAN INTERNAL DAN PERANCANGAN SISTEM INFORMASI PENJUALAN DAN PEMBELIAN PADA UD ADI PUTRA MENGGUNAKAN METODE PROTOTYPE - Ni Made Esa Purnama Sari; Nengah Widya Utami; Ni Putu Noviyanti Kusuma (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This study aims to analyze and design an accounting information system for sales and purchases at UD Adi Putra, a trading business specializing in building materials that currently relies on manual recording. The method used is the prototype method, which includes system requirements identification, system design, prototype development, evaluation and improvement, and finalization of the prototype. The results show that the current manual system leads to calculation errors, lost receipts, and inaccurate reports. The proposed system includes the design of flowcharts, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and a more effective database design. Evaluation through beta testing indicates that the new system prototype is user-friendly and meets user needs, significantly enhancing the company's operational efficiency and accuracy.